Specific Features of Development of the Infectious Process Caused by Cultivable and Non Cultivable Bacteria in the Presence of Experimental Burn Injury - S. P. Sakharov; L. B. Kozlov (Общая реаниматология, 2015)
Objective: to study a trend in the development of the infectious process caused by cultivable and non cultivable bacteria in Chinchilla rabbits with burn disease. Materials and methods. The investigators examined 64 rabbits subcutaneously infected with cultivable and non cultivable Pseudomonas aeruginosa and Staphylococcus aureus at a dose of 105 microbial cells in the presence of burn injury in experimental groups and in two similar control groups of animals without thermal injury. Rabbits were exposed to IIIAB degree burn injury under anesthesia. The non cultivable bacteria were obtained by the procedure proposed by L. B. Kozlov et al., by applying a refrigerated heating circulator. The trend in the development of the infectious process was observed during 21 days. Dead animals were dissected; bacterial concentrations were estimated in their viscera and abnormal changes were determined in the histological specimens. The results of the investigations were statistically processed according to STATISTICA 6.0 using the mean arithmetic error (М±m). Differences were statistically evaluated by Student’s t test and the Mann Whitney test. A correlation analysis was made applying the software package Microsoft Excel 97 for IBM PC to compute correlation coefficients and their errors. Results. The cultivable bacteria in the animals with burn injury induced an infectious process in their viscera to develop sepsis on days 8—12 of the disease with a fatal outcome and the non cultivable bacteria in those with burn disease caused death due to brain injury on days 2—3, with P.aeruginosa isolated from brain tissue. Conclusion. Both the cultivable and non cultivable bacteria had significant effects in Chinchilla rabbits with burn disease. Non cultivable P.aeruginosa had a tropism for nerve tissue, which was not found in the cul tivable bacteria.